West African Masking Traditions and Diaspora Masquerade Carnivals : History, Memory, and Transnationalism. - Njoku, Raphael Chijioke. (Rochester Studies in African History and the Diaspora Series, 2020)
A revisionist account of African masquerade carnivals in transnational context that offers readers a unique perspective on the connecting threads between African cultural trends and African American cultural artifacts.